2005
DOI: 10.1158/0008-5472.can-04-4510
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Tumor Development and Metastasis Formation in Mice Lacking the S100A4(mts1) Gene

Abstract: The S100A4(mts1) protein stimulates metastatic spread of tumor cells. An elevated expression of S100A4 is associated with poor prognosis in many human cancers. Dynamics of tumor development were studied in S100A4-deficient mice using grafts of CSML100, highly metastatic mouse mammary carcinoma cells. A significant delay in tumor uptake and decreased tumor incidences were observed in S100A4(À/À) mice compared with the wild-type controls. Moreover, tumors developed in S100A4(À/À) mice never metastasize. Immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
156
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 208 publications
(165 citation statements)
references
References 45 publications
(64 reference statements)
8
156
0
1
Order By: Relevance
“…Through specific communication with cancer cells, CAFs can directly promote tumor initiation, progression and metastasis (Dimanche-Boitrel et al, 1994;Olaso et al, 1997;Olumi et al, 1999;Bhowmick et al, 2004;Kuperwasser et al, 2004;Grum-Schwensen et al, 2005;Orimo et al, 2005). CAFs secrete growth factors and ECM-degrading proteases to promote tumor growth and invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Through specific communication with cancer cells, CAFs can directly promote tumor initiation, progression and metastasis (Dimanche-Boitrel et al, 1994;Olaso et al, 1997;Olumi et al, 1999;Bhowmick et al, 2004;Kuperwasser et al, 2004;Grum-Schwensen et al, 2005;Orimo et al, 2005). CAFs secrete growth factors and ECM-degrading proteases to promote tumor growth and invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence shows that stromal cells may not be passive bystanders but might have an important role in modifying tumor growth. Many functional studies have demonstrated the importance of fibroblasts in cancer initiation 1 , progression [2][3][4] and metastases 5 . In animal models of prostate and breast cancers, oncogene-modified epithelial cells became malignant or showed enhanced growth when coinoculated with fibroblasts that were either oncogene induced 6 or derived from fresh human carcinoma tissues 2,3 (that is, CAFs).…”
mentioning
confidence: 99%
“…1). Recently, it was shown that fibroblast-produced FSP-1 promotes tumor metastasis and that mammary carcinoma cells injected into FSP-1 -/-mice showed significant delay in tumor uptake and decreased tumor incidence 15 . Interestingly, coinjection of carcinoma cells with FSP-1 +/+ mouse embryonic fibroblasts (MEFs) partially restored the kinetics of tumor development and the ability to form metastases.…”
mentioning
confidence: 99%